Implementasi Kurikulum Berbasis Cinta melalui Metode Deep Learning (Mindful, Meaningful, Joyful) dalam Pembelajaran Bahasa Indonesia di MIN 10 Bandar Lampung - Siti Anisa; Marzuki Noor; Sutrisni Andayani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to describe the implementation of the Love-Based Curriculum through the deep learning method in Indonesian language learning at MIN 10 Bandar Lampung and to analyze its impact on students’ language skills. The research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation involving the principal, Indonesian language teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the Love-Based Curriculum was carried out through the integration of the Five Love Values (Panca Cinta) into Indonesian language learning activities combined with mindful, meaningful, and joyful learning approaches. Love for Allah and the Prophet was developed through exemplary texts, love of knowledge through literacy habituation and reflection activities, love for the environment through experience-based writing activities, love for oneself and others through collaborative discussions, and love for the homeland through the use of local folktales. The application of the deep learning method created a more active, enjoyable, and meaningful learning atmosphere, resulting in improvements in students’ reading comprehension, speaking, writing, and listening skills. In addition, the study identified several challenges, including limited learning media, differences in students’ characteristics, time constraints, and uneven teacher understanding of the Love-Based Curriculum concept. This study concludes that the implementation of the Love-Based Curriculum through the deep learning method is capable of creating Indonesian language learning that not only focuses on language skill mastery but also strengthens students’ character and humanitarian values holistically.